Maternal Genetic Composition of a Medieval Population from a Hungarian-Slavic Contact Zone in Central Europe. - Veronika Csákyová; Anna Szécsényi-Nagy; Aranka Csősz; Melinda Nagy; Gabriel Fusek; Péter Langó; Miroslav Bauer; Balázs Gusztáv Mende; Pavol Makovický; Mária Bauerová (PLoS ONE, 2016)
The genetic composition of the medieval populations of Central Europe has been poorly investigated to date. In particular, the region of modern-day Slovakia is a blank spot in archaeogenetic research. This paper reports the study of mitochondrial DNA (mtDNA) in ancient samples from the 9th-12th centuries originating from the cemeteries discovered in Nitra-Šindolka and Čakajovce, located in western Slovakia (Central Europe). This geographical region is interesting to study because its medieval multi-ethnic population lived in the so-called contact zone of the territory of the Great Moravian and later Hungarian state formations. We described 16 different mtDNA haplotypes in 19 individuals, which belong to the most widespread European mtDNA haplogroups: H, J, T, U and R0. Using comparative statistical and population genetic analyses, we showed the differentiation of the European gene pool in the medieval period. We also demonstrated the heterogeneous genetic characteristics of the investigated population and its affinity to the populations of modern Europe.